KEMANDIRIAN KELUARGA DALAM MELAKUKAN FOOT CARE PADA PENDERITA DIABETES MELLITUS DI WILAYAH KERJA PUSKESMAS KEDUNG DORO SURABAYA - Ernawati, Dwi (Jurnal Keperawatan Malang, 2020)
Background: The complication of diabetes mellitus is diabetic foot injury. The inability of the family to do foot care is caused by several factors, namely knowledge, socioeconomic and family support. Family independence is very necessary in the success of foot care in diabetic patients undergoing foot care at home. The aim was to determine the level of independence of the family in doing foot care in patients with diabetes mellitus in the working area of ??the Kedung Doro Health Center in Surabaya. Aim: This research design used descriptive method. The sampling was done by simple random sampling method and obtained a number of 92 respondents, the instrument of family independence using a questionnaire. Data is presented in the form of a frequency distribution tabulation. Method: This research design used descriptive method. The sampling was done by simple random sampling method and obtained a number of 92 respondents, the instrument of family independence using a questionnaire. Data is presented in the form of a frequency distribution tabulation. Results: The results indicate that the independence of respondents in the category of independence 4 is 31.5%, independence 2 is 29.3%, independence 3 is 20.7% and independence I is 18.5%. Conclusion: Families should actively participate together with health workers in health centers in increasing independence to care for family members suffering from diabetes mellitus, especially in performing foot care to prevent diabetes foot injuries and further complications.